OPEC's Market Power: An Empirical Dominant Firm Model for the Oil Market - Rolf Golombek; Alfonso Irarrazabal; Lin Ma (Norges Bank, 2014)
In this paper we estimate a dominant firm-competitive fringe model for the crude oil market using quarterly data on oil prices for the 1986-2009 period. All the estimated structural parameters have the expected sign and are significant at standard test levels. We find that OPEC exercised its market power during the sample period. Counterfactual experiments indicate that world GDP is the main driver of long-run oil prices, however, supply (depletion) factors have become more important in recent years.
hdl:11250/2495982
Keywords: L13; L22; Q31; 330; OPEC; Lerner index; oil; dominant firm; market power; oil demand elasticity; oil supply elasticity